Electrophoretic Mobility Shift Assay of in vitro Phosphorylated RNA Polymerase II Carboxyl-terminal Domain Substrates - Mayfield, Joshua E. (Bio-Protocol, 2020)

(untitled) (Bio Protoc)
Eukaryotic RNA polymerase II transcribes all protein-coding mRNAs and is highly regulated. A key mechanism directing RNA polymerase II and facilitating the co-transcriptional processing of mRNAs is the phosphorylation of its highly repetitive carboxyl-terminal domain (CTD) of its largest subunit, RPB1, at specific residues. A variety of techniques exist to identify and quantify the degree of CTD phosphorylation, including phosphorylation-specific antibodies and mass spectrometry. Electrophoretic mobility shift assays (EMSAs) have been utilized since the discovery of CTD phosphorylation and continue to represent a simple, direct, and widely applicable approach for qualitatively monitoring CTD phosphorylation. We present a standardized method for EMSA analysis of recombinant GST-CTD substrates phosphorylated by a variety of CTD kinases. Strategies to analyze samples under both denatured/reduced and semi-native conditions are provided. This method represents a simple, direct, and reproducible means to monitor CTD phosphorylation in recombinant substrates utilizing equipment common to molecular biology labs and readily applicable to downstream analyses including immunoblotting and mass spectrometry.